ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT INVESTASI DI PASAR MODAL PADA MAHASISWA EKONOMI DAN BISNIS (Studi Pada Mahasiswa Aktif Sekolah Tinggi Ilmu Ekonomi Malangkuçeçwara Tahun 2021) - IRAWAN BUDI PRASETYO; SUSANTI SUSANTI (UNHI Press, 2023)
The purpose of this study was to determine the effect of investment education, minimum investment capital, perceived return, perceived risk, and social media on investment interest in the capital market among students at the Malangkucecwara College of Economics. This type of research is quantitative research that uses primary data and is generated from the distribution of questionnaires. The population of this study is active students in 2021, Malangkucecwara College of Economics with a sample of 91 students as respondents. The statistical method is multivariate analysis using SmartPLS. The results of this study are investment education factors, minimum investment capital factors, and risk perceptions do not have a significant influence on the variables of interest in investment in the capital market for students of the Malangkucecwara College of Economics. Meanwhile, the perception of return and social media have a significant influence on the variable of interest in investing in the capital market for students of the Malangkucecwara College of Economics.